P183 Comparison of patient satisfaction between endobronchial ultrasound and flexible bronchoscopy performed under conscious sedation: a prospective study. (2nd December 2011) - Huq, S; Smyth, C; Kazmi, S; Giles, T; Walshaw, M; Binukrishnan, S; Mohan, K
Abstract : Background: Endobronchial ultrasound-guided transbronchial needle aspiration (EBUS-TBNA) is increasingly performed by respiratory physicians across the UK. Although patient satisfaction with flexible bronchoscopy (FB) is high, there are no studies comparing patient satisfaction with FB vs EBUS performed under conscious sedation. Methods: In this prospective study, patients completed a questionnaire 2 h post-procedure when they were fully awake as determined by the modified Aldrete score. The questionnaire consisted of a 4-point Likert scale to record the degree of discomfort and a 5-point scale to record the overall satisfaction and willingness to return for the procedure. Both EBUS and FB were performed using topical lignocaine and intravenous midazolam. EBUS was performed by a consultant physician, whereas FB was performed by a consultant physician or a specialty registrar. Results: 52 consecutive patients (mean age 65) undergoing EBUS and 35 patients (mean age 66) undergoing FB completed the study. Although the mean dose of intravenous midazolam used in the EBUS group was higher (3.16 mg vs 2.52 mg; p<0.01), the level of sedation (determined by sedation score of 0-unresponsive to 6-agitated) pre-scope insertion was similar in both groups. The mean dose of topical lignocaine (excluding oropharyngeal lignocaine) was also similar in both groups. The duration of procedure with EBUS was longer compared to FB (21.25 min vs 12.09 min; p<0.001). Despite this, there were no significant differences in the reported patient discomfort with anaesthetic throat spray, transtracheal lignocaine injection or scope insertion. Similarly, there were no significant differences in the reported incidence of cough, dyspnoea, throat pain, chest pain, feeling of suffocation and overall tolerance of the procedure. The overall satisfaction for the procedure was 95% in the EBUS group and 89% in the FB group, while 92% and 86% respectively were willing to have the procedure again if needed. EBUS was diagnostic in 96% (mean lymph node size 1.6 cm) and there were no complications. Conclusion: Patient satisfaction with EBUS-TBNA under conscious sedation is high. As EBUS services continue to expand, physicians can perform this under conscious sedation with similar patient satisfaction level as experienced with FB.